Evaluation of the crack-healing performance and durability of bacteria integrated alkali-activated fly ash composites. (15th August 2022) - Sarkar, Manas; Maiti, Moumita; Malik, Muhammad Akbar; Xu, Shilang
Abstract: This study aims to introduce Bacillus Cohnii endospores into an alkali-activated fly ash-based composite (AAFC) to improve the crack-healing properties and durability while maintaining an environment-friendly strategy. Few important parameters such as water absorption capacity, sulfate resistivity, rapid chloride ions penetration, and its migration through bacteria impregnated AAFC (Bio-AAFC) are considered for the assessment of the healed structure's activities. The cracks up to 0.59 mm width dimension are completely plugged up and 12% of mechanical strength of healed-AAFC is regained within 28 days, determined in the microscopic study, strength gains calculation, and velocity of ultrasonic pulse waves assessment. Bio-mineral precipitation into Bio-AAFC produces durable concrete, particularly in chloride and sulfate-laden environments. Due to calcium/sodium carbonate precipitation in pores and voids, the microstructure of the biosystem became compact and dense, resulting in excellent performances. It is the microbial activity for the biomineralization process that causes mainly calcium carbonate deposition to reduce pore size (35% average 510 nm pore diameter) in Bio-AAFC samples, thereby verifying the bacterial endospores can persist for a long time inside AAFC. Specifically, Bio-AAFC, having magnificent durability and crack-healing abilities explores the recycling of industrial dry wastes in a promising way. Graphical abstract: Image 1 Highlights: Bacillus Cohnii endospores is introduced to alkali activated fly ash based building composite for MICP. Crack repairing and degree of healing, porosity and durability of the healed structures are investigated. 0.59 mm width crack is completely plugged up and 12% strength is regained in 28days.